Simultaneous Toll Road Public Infrastructure and its Transaction Volume in Non-Taxable State Revenue a Case Study at PT. Hutama Karya Persero - Effendi, Adang Djatnika; Patronimik, Baktybek; Judijanto, Loso; Sujoko, Sujoko; Christianto, Reinardus Dwi Prio (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: Toll roads are vital transportation infrastructure in improving connectivity between regions in Indonesia. Apart from being a means of transportation, toll roads also contribute to state revenue through non-tax state revenue (PNBP). However, there are still limitations in understanding the extent to which toll road length and traffic volume affect PNBP.Methodology: This research uses a quantitative approach with descriptive methods. The data used is time series data from 2013 to 2023 which includes toll road length, traffic volume, and PNBP managed by PT Hutama Karya (Persero). The analysis was carried out using linear regression to test the relationship between these variables.Finding: The results showed that there is a significant relationship between the length of toll roads and traffic volume to PNBP. The increase in toll road length and traffic volume simultaneously contributes to the increase in PNBP. In addition, toll road construction also has a positive impact on local economic growth and economic diversification of communities around toll roads.Conclusion: Toll roads not only serve as a means of transportation, but also a significant source of state revenue. Therefore, this study recommends strategies to improve the efficiency of toll road infrastructure management to optimize PNBP revenue and encourage broader economic growth.